Restricted distribution of mrg‐1 mRNA in C. elegans primordial germ cells through germ granule‐independent regulation. (3rd September 2015) - Miwa, Takashi; Takasaki, Teruaki; Inoue, Kunio; Sakamoto, Hiroshi
Abstract : The chromodomain protein MRG‐1 is an essential maternal factor for proper germline development that protects germ cells from cell death in C. elegans . Unlike germ granules, which are exclusively segregated to the germline blastomeres at each cell division from the first cleavage of the embryo, MRG‐1 is abundant in all cells in early embryos and is then gradually restricted to the primordial germ cells (PGCs) by the morphogenesis stage. Here, we show that this characteristic spatiotemporal expression pattern is dictated by the mrg‐1 3'UTR and is differentially regulated at the RNA level between germline and somatic cells. Asymmetric segregation of germ granules is not necessary to localize MRG‐1 to the PGCs. We found that MES‐4, an essential chromatin regulator in germ cells, also accumulates in the PGCs in a germ granule‐independent manner. We propose that C. elegans PGCs have a novel mechanism to accumulate at least some chromatin‐associated proteins that are essential for germline immortality. Abstract : MRG‐1 is an essential chromatin factor for germline development in C. elegans. We found that the spatiotemporal distribution of MRG‐1 is regulated primarily through its 3'UTR by stabilizing mrg‐1 mRNA in all blastomeres in early embryos and in PGCs alone in later embryos, in a P granule‐independent manner.